IMPLEMENTASI IMPLEMENTASI TERTIB ADMINISTRASI KEPENDUDUKAN DAN RELEVANSINYA DENGAN KONSEP ASAS-ASAS UMUM PEMERINTAHAN YANG BAIK (GOOD GOVERNANCE) DALAM KONSEP NEGARA HUKUM - Sumartini, R. Siti; Arifin, Jajang; Abas, Suhendar; Nursidi, Didi (Yustitia, 2024)
Population administration is an important issue for a country. This is because residents and citizens are essential elements of a country. Furthermore, based on data from the Central Statistics Agency (BPS), Indonesia's population in 2023 is projected to be 278.8 million people, of course this large number demands that population administration be carried out properly and correctly. In line with the concept of the rule of law and the principles of good governance. Based on this, a legal problem arises, related to how the orderly implementation of population administration is linked to the concept of the rule of law and how the principles of good governance can provide services to the public related to the orderly implementation of population administration. Population administration is a series of structuring and controlling activities in the publication of population documents and data through population registration, civil registration, management of population administration information and utilization of the results for public services and development of other sectors. In essence, the state is obliged to provide protection and recognition for the determination of personal status and legal status for every Population Event and Important Event experienced by residents inside or outside the territory of the Unitary State of the Republic of Indonesia. For the state, the importance of population documents is aimed at accessing public services. , Development planning, and Legal allocation